1999
DOI: 10.1159/000045290
|View full text |Cite
|
Sign up to set email alerts
|

VCAM-1, ICAM-1, and E-Selectin in IgA Nephropathy and Schönlein-Henoch Syndrome: Differences between Tissue Expression and Serum Concentration

Abstract: The tissue expressions of vascular cell adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1) and endothelial leukocyte adhesion molecule 1 (E-selectin-1) were investigated in biopsy specimens from 28 patients with different stages of IgA nephropathy (IgAN) and 20 patients with acute renal failure (ARF) or chronic renal diseases (amyloidosis, Alport’s glomerulopathy) by immunohistochemistry. The results were compared with the serum levels of the three adhesion molecules. VCAM-1 expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…In addition, the expression of ICAM-1 is induced on the proximal tubule epithelium associated with glomerular [18]and interstitial cellular infiltration seen by light microscopy [13]and characterized by monoclonal antibodies directed to leukocytes [20, 26]. The serum ICAM-1 levels in histologically severe forms [27]and in both exacerbating clinical episodes and during quiescence [26, 28]are similar to those in healthy controls. Thus, the abnormal expression of ICAM-1 on the tubular epithelium appears to be a specific local phenomenon rather than a reflection of the serum level, but its significance is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of ICAM-1 is induced on the proximal tubule epithelium associated with glomerular [18]and interstitial cellular infiltration seen by light microscopy [13]and characterized by monoclonal antibodies directed to leukocytes [20, 26]. The serum ICAM-1 levels in histologically severe forms [27]and in both exacerbating clinical episodes and during quiescence [26, 28]are similar to those in healthy controls. Thus, the abnormal expression of ICAM-1 on the tubular epithelium appears to be a specific local phenomenon rather than a reflection of the serum level, but its significance is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…One such molecule, VCAM-1, is expressed on the surface of endothelial cells and promotes the binding and movement of lymphocytes and eosinophils across vascular endothelium (1)(2)(3). VCAM-1-mediated leukocyte recruitment and migration are implicated in the pathogenesis of several disease states, including inflammatory bowel disease (4), conjunctivitis (5), nephropathy (6,7), and arthritis (8). The essential role of VCAM-1 in tissue injury has been corroborated in a number of animal models.…”
mentioning
confidence: 99%
“…26,[29][30][31][32][33][34] In addition, elevated circulating VCAM-1 has been shown to be correlated with increased VCAM-1 expression from renal biopsy in IgA nephropathy. 35 E-selectin is also found to be a strong predictor of severely increased albuminuria and coronary artery disease in patients with type 1 diabetes. 36,37 In another study VCAM-1 and E-selectin showed positive associations with retinopathy, albuminuria, and CVD.…”
Section: Discussionmentioning
confidence: 94%